PENGARUH LITERASI PAJAK DAN PEMANFAATAN APLIKASI PERPAJAKAN TERHADAP KEPATUHAN PAJAK PADA DOSEN FAKULTAS KESEHATAN UNIVERSITAS ADIWANGSA JAMBI - Echin Xizley Orlanda; Haviz Taufik; Aditya Pradana (STKIP Subang, 2026)
This study aims to analyze the influence of tax literacy and the utilization of tax applications on tax compliance among lecturers at the Faculty of Health, Universitas Adiwangsa Jambi. This research employed a quantitative approach using a purposive sampling technique involving 30 respondents who possess a Taxpayer Identification Number (NPWP) and independently fulfill their tax reporting obligations. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that tax literacy does not have a significant partial effect on tax compliance (Sig. = 0.440 > 0.05), while the utilization of tax applications has a significant positive effect on tax compliance (Sig. = 0.007 < 0.05). Simultaneously, tax literacy and the utilization of tax applications significantly affect tax compliance (Sig. = 0.011 < 0.05). The coefficient of determination (R²) of 0.282 indicates that both independent variables explain 28.2% of the variation in tax compliance, while the remaining 71.8% is influenced by other factors outside this study. These findings suggest that the ease of using tax applications plays an important role in improving tax compliance, whereas tax literacy requires support from other factors to produce a stronger influence on taxpayers' compliance.